Circular RNA FOXP1 Induced by ZNF263 Upregulates U2AF2 Expression to Accelerate Renal Cell Carcinoma Tumorigenesis and Warburg Effect through Sponging miR-423-5p - Li Fang; Ting Ye; Yanmei An (Journal of Immunology Research)
Renal cell carcinoma (RCC), as one of the most common malignant tumors in the urinary system, is featured with high morbidity and mortality. Although the improvement of clinical intervention, such as surgery technology, chemotherapy, and radiotherapy, has been made, the outcomes of RCC patients are still poor. Novel targets for RCC treatment are urgently needed. Recently, circRNA has been in-depth studied and is considered as a promising direction for gene target therapy. In this study, we explored the function of circFOXP1 in RCC progression and its underlying mechanisms. Firstly, we demonstrated the characterization and expression of circFOXP1 in RCC tissues and cells. Next, by conducting a serial experiment, we found that downregulated circFOXP1 inhibited cell proliferation, migration, invasion, and the Warburg effect. Next, our experiments found that circFOXP1 upregulated U2AF2 expression via sponging miR-423-5p in RCC cells. Moreover, we found that ZNF263 induced circFOXP1 expression in RCC cells. To sum up, our study partially demonstrated that the novel ZNF263/circFOXP1/miR-423-5p/U2AF2 axis has a role in RCC progression. Our results might provide a new direction for RCC therapeutic target exploring.